2003
DOI: 10.1097/01.brs.0000090833.96168.3f
|View full text |Cite
|
Sign up to set email alerts
|

C5 Palsy after Decompression Surgery for Cervical Myelopathy

Abstract: The incidence of postoperative C5 palsy has been reported at 4.6% after surgery for cervical compression myelopathy and this value has not varied with different surgical procedures or disease etiologies. The pathogenesis of postoperative C5 palsy remains unclear at the present time. Patients with postoperative C5 palsy generally have a good prognosis for functional recovery, but the severely paralyzed cases required significantly longer recovery times than the mild cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
264
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(278 citation statements)
references
References 21 publications
(34 reference statements)
8
264
2
3
Order By: Relevance
“…There are some common characteristics between the late postoperative neurological deficits in the present study and C5 palsy after cervical laminoplasty [24]. The common features were: (1) late onset after surgery, (2) unilateral weakness of the deltoid and biceps brachii muscles with or without sensory disturbance, and (3) preceding severe pain of the neck and scapular arch.…”
Section: Discussionsupporting
confidence: 49%
“…There are some common characteristics between the late postoperative neurological deficits in the present study and C5 palsy after cervical laminoplasty [24]. The common features were: (1) late onset after surgery, (2) unilateral weakness of the deltoid and biceps brachii muscles with or without sensory disturbance, and (3) preceding severe pain of the neck and scapular arch.…”
Section: Discussionsupporting
confidence: 49%
“…This technique is well established and the reported complication rates are acceptable, but some problems such as axial symptoms or C5 palsy have not been fully resolved [4][5][6]. The long term results of this technique is satisfactory, with the preservation of the enlarged cervical canal area and the maintenance of JOA scores for cervical myelopathy (JOA score, Table 1, maximum score 17 points) [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported after other posterior-based techniques. The incidence varies from 0-50% depending on the technique used, how the condition is defined and which patient group is being analysed [3,[4][5][6][7][8]9,10]. Takemitsu et al [11] reported a higher incidence among patients undergoing instrumentation than those treated by laminoplasty alone.…”
Section: Introductionmentioning
confidence: 99%
“…Several etiologies have been proposed to explain this phenomenon including direct root injury, posterior spinal cord drift, spinal cord ischemia, reperfusion injury and segmental cord affection [4,[7][8][9]. Additional instrumentation is suspected of increasing the incidence of C5 palsy through iatrogenic foraminal stenosis [12,5,6,10] and added tension in the spinal cord and roots caused by correcting the spinal alignment [6,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation